Влияние высокожировых рационов с различным жирнокислотным составом на содержание незаменимых жирных кислот в липидах печени = Influence of high fat diets with different composition of fatty acids on the content of essential fatty acids in liver lipids - Levitsky, A. P.; Khodakov, I. V.; Levchenko, E. M. (Journal of Education, Health and Sport, 2015)
Levitsky A. P., Khodakov I. V., Levchenko E. M. Влияние высокожировых рационов с различным жирнокислотным составом на содержание незаменимых жирных кислот в липидах печени = Influence of high fat diets with different composition of fatty acids on the content of essential fatty acids in liver lipids. Journal of Education, Health and Sport. 2015;5(12):598-607. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.44266 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A598-607 http://pbn.nauka.gov.pl/works/687268 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.12.2015. Revised 15.12.2015. Accepted: 29.12.2015. УДК 612.397.23+577.16+613.2 ВЛИЯНИЕ ВЫСОКОЖИРОВЫХ РАЦИОНОВ С РАЗЛИЧНЫМ ЖИРНОКИСЛОТНЫМ СОСТАВОМ НА СОДЕРЖАНИЕ НЕЗАМЕНИМЫХ ЖИРНЫХ КИСЛОТ В ЛИПИДАХ ПЕЧЕНИ INFLUENCE OF HIGH FAT DIETS WITH DIFFERENT COMPOSITION OF FATTY ACIDS ON THE CONTENT OF ESSENTIAL FATTY ACIDS IN LIVER LIPIDS А. П. Левицкий1, И. В. Ходаков1, Е. М. Левченко2 A. P. Levitsky1, I. V. Khodakov1, E. M. Levchenko2 1ГУ «Институт стоматологии НАМН», г. Одесса 2КУ «Одесская областная клиническая больница» 1SE«The Institute of Stomatology of the National acаdemie of medical science of Ukraine», Odessa, Ukraine 2Municipal Institution «Odessa Regional Clinical Hospital» Abstract Aim: To determine the effect of high fat diets with different fatty acid composition on the level of essential fatty acids in the liver. Materials and Methods: We used sunflower, olive, palm oil or butter in the amount of 15% for a high fat diet (HFD). The experiment was carried out in rats for 41 days. In the liver there was determined the content of total lipids (TL), free fatty acids (FFA) and the content of essential fatty acids by the chromatographic method. Results: HFD increases the TL content in the liver (excluding butter) and reduces the level of FFA. HFD reduces the TL content, and it reduces a lot the essential fatty acids’ content in FFA, especially linoleic and eicosapentaenoic acids. Conclusion: Perhaps HFD inhibits lipolysis in the liver and inhibits the synthesis of essential fatty acids. Keywords: fatty food, fatty acids, liver. Резюме Дополнительное введение в базовый комбикорм 15 % подсолнечного, оливкового, пальмового или сливочного масла снижает в печени уровень свободных жирных кислот (СЖК) и содержание незаменимых жирных кислот (особенно, линоленовой и эйкозапентаеновой), причем более существенно во фракции СЖК. Ключевые слова: жировое питание, жирные кислоты, печень.